HUBUNGAN KECUKUPAN VITAMIN D DENGAN SATURASI OKSIGEN PADA PASIEN COVID-19 - Fitra Aslami Ghifari; Amelya Augusthina Ayusari; Risalina Myrtha; Dwi Rahayu (Biomedika, 2023)
ABSTRACT Coronavirus Disease 2019 (COVID-19) infection is a global health problem with rapid transmission and variable prognosis. Oxygen saturation is an indicator for assessing the prognosis of COVID-19 infection. Viral infections are related to the immune system because they are self-limiting diseases. Vitamin D is considered able to improve the immune system through several pathways. There are differences in research results regarding vitamin D and respiratory tract infections. This study aims to determine the relationship between vitamin D adequacy and oxygen saturation in COVID-19 patients at X Surakarta Hospital. This research was an observational analysis with a cross-sectional design on 32 patients who had been treated for COVID-19 at RS X Surakarta. Data on oxygen saturation and vitamin D management were taken from medical records, while food consumption data was completed by filling in a formulary food frequency questionnaire (FFQ). Data analysis used the Chi-Square test (α=0.05). The research results showed that there was no significant relationship (p=0.055) between vitamin D adequacy and oxygen saturation in COVID-19 patients (p>0.05). The conclusion of this study was no relation between vitamin D adequacy and oxygen saturation in COVID-19 patients.   ABSTRAK Infeksi Coronavirus Disease 2019 (COVID-19) merupakan permasalahan kesehatan global dengan penularan cepat dan prognosis bervariasi. Saturasi oksigen merupakan salah satu indikator untuk menilai prognosis infeksi COVID-19. Infeksi virus berkaitan dengan sistem imun karena bersifat self-limiting disease. Vitamin D dinilai dapat meningkatkan sistem imun melalui beberapa jalur. Terdapat perbedaan hasil penelitian mengenai vitamin D dan infeksi saluran pernapasan. Penelitian ini bertujuan untuk mengetahui hubungan kecukupan vitamin D dengan saturasi oksigen pasien COVID-19 di RS X Surakarta. Penelitian ini bersifat analisis observasional dengan rancangan cross-sectional terhadap 32 pasien yang pernah dirawat COVID-19 di RS X Surakarta. Data saturasi oksigen dan tatalaksana vitamin D diambil dari rekam medis, sedangkan data konsumsi pangan dengan pengisian formular food frequency questionnaire (FFQ). Analisis data menggunakan uji Chi-Square (α=0,05). Hasil penelitian menunjukkan bahwa tidak terdapat hubungan yang signifikan (p=0,055) antara kecukupan vitamin D dengan saturasi oksigen pada pasien COVID-19 (p>0,05). Kesimpulan penelitian ini bahwa kecukupan vitamin D tidak berhubungan dengan saturasi oksigen pasien COVID-19.